2019
DOI: 10.1007/s13770-019-00224-9
|View full text |Cite
|
Sign up to set email alerts
|

A Platform for Studying of the Three-Dimensional Migration of Hematopoietic Stem/Progenitor Cells

Abstract: BACKGROUND: Hematopoietic stem/progenitor cells (HSPCs) have the property to return to the bone marrow, which is believed to be critical in situations such as HSPC transplantation. This property plays an important role in the stemness, viability, and proliferation of HSPCs, also. However, most in vitro models so far have not sufficiently simulated the complicate environment. Here, we proposed a three-dimensional experimental platform for the quantitative study of the migration of HSPCs. METHODS: After encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We next evaluate the influence of elevated atmospheric pressure on mesoderm lineage commitment. Physical force in the form of shear stress has been leveraged to enhance ESC differentiation to endothelial progenitor and hematopoietic lineages (Wolfe and Ahsan, 2013), and a combination of osteoblasts and intermittent hydrostatic pressure has been used to show an influence on HSPC migration (Kim et al, 2019; Lee et al, 2020), however no studies have implemented hydrostatic pressure to generate HSPCs from pluripotent stem cells on their own. We differentiated iPSCs to HSPCs expressing CD34, CD43, and CD45 using a bi-phasic oxygen concentration protocol to simulate in-vivo HSPC development.…”
Section: Resultsmentioning
confidence: 99%
“…We next evaluate the influence of elevated atmospheric pressure on mesoderm lineage commitment. Physical force in the form of shear stress has been leveraged to enhance ESC differentiation to endothelial progenitor and hematopoietic lineages (Wolfe and Ahsan, 2013), and a combination of osteoblasts and intermittent hydrostatic pressure has been used to show an influence on HSPC migration (Kim et al, 2019; Lee et al, 2020), however no studies have implemented hydrostatic pressure to generate HSPCs from pluripotent stem cells on their own. We differentiated iPSCs to HSPCs expressing CD34, CD43, and CD45 using a bi-phasic oxygen concentration protocol to simulate in-vivo HSPC development.…”
Section: Resultsmentioning
confidence: 99%
“…By seeding cells on a stretchable micropost array (SµPA) cytometry, Weng et al employed varying degrees of defined static equibiaxial cell stretches [163]. Alginate beads with osteoblasts encapsulated were used to bio-mimic the low 3D stiffness of the BM niche [209]. The application of intermittent hydrostatic pressure (IHP) also is a widely used approach to simulate the BM mechanical microenvironment [69,209,210].…”
Section: In-vitro Mechanical Mimicry Platforms For Hsc Supportmentioning
confidence: 99%
“…Several scaffolds can be loaded with SP1 or SP as chemoattractants to guide endogenous stem cells to the site of injury. [16][17][18][19] To apply the newly discovered SP1 in regenerative medicine, an electrostatically interactive hydrogel was used as a scaffold to load SP1.…”
Section: Sp Has Been Shown To Induce Endocytosis and Recycle Nk1rmentioning
confidence: 99%
“…Some in vivo studies have reported that SP scaffolds synergistically increase the migration of endogenous stem cells toward the scaffold. [16][17][18][19] Among the many types of scaffolds developed thus far, injectable hydrogels are widely used in tissue engineering due to the advantages of being in a liquid state before injection. Therefore, various physiologically active substances can be easily mixed into the hydrogel and injected in a noninvasive fashion without the need for surgery.…”
Section: Introductionmentioning
confidence: 99%